Aspirations and the role of social protection: evidence from a natural disaster in rural Pakistan - Kosec, Katrina; Mo, Cecilia Hyunjung (Elsevier, 2017)
Citizens’ aspirations are increasingly recognized as an important dimension of their well-being. Those with high aspirations set ambitious goals for themselves, and those with low aspirations may fall prey to a poverty trap. Do natural disasters negatively impact aspirations? If so, can governments blunt these effects? We consider Pakistan’s devastating 2010 floods—and the government’s uneven relief efforts—to analyze these questions. We first show that the extreme rainfall generating this disaster significantly reduced aspirations, even when current levels of household expenditure, wealth, and education are taken into account. Individuals experiencing 2010 monsoon season rainfall that was one standard deviation higher than average had aspiration levels 1.5 years later that were 0.15 standard deviations lower than those of similar individuals experiencing just average levels of rainfall. This is the same negative shock to aspirations that one would experience as a result of a 50% reduction in household expenditures. Moreover, the negative effect of natural disasters on aspirations is especially strong among the poor, and among those who are most vulnerable to weather shocks. However, exploiting exogenous variation in flood relief access, we show that government social protection can attenuate these negative impacts. Individuals in villages that received Citizens Damage Compensation (Watan Card) Program flood relief—providing cash equivalent to 9.4% of annual household expenditures in each of the three years following the disaster—saw significantly lower declines in aspirations than did those in similarly affected villages without this relief. This offers a new understanding of social protection; it not only restores livelihoods and replaces damaged assets, but also has an enduring effect by easing mental burdens, and thus raising aspirations for the future. The negative effects of natural disasters and the efficacy of government relief programs may thus be underestimated if aspirations are ignored.